2018
DOI: 10.3390/catal8090348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Drying, Calcination and Aging of Pt/Al2O3 on Platinum Dispersion

Abstract: The effect of heating method employed for drying and calcination during the synthesis of 1 wt% Pt/Al2O3 catalyst was investigated. Conventional heating (CH) in resistive oven and microwave heating (MW) in single mode were applied, and the Pt dispersion and Brunauer-Emmett-Teller (BET) surface area were measured to characterize the samples. It was evidenced that the fast and homogeneous heating offered by the microwave heating led to higher Pt dispersion. However, this benefit was only achieved when the subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The Pd catalyst in this case was taken over by Pt and Rh catalysts due to their higher stability upon sintering and their ability to maintain the active site unaltered during the treatment prior reaction and therefore. X. Auvray and A. Thuault [7] chose the Pt/Al 2 O 3 catalyst to study the effect of microwave pretreatment over precious metal dispersion. The microwave heating was compared to the conventional method of drying and calcination.…”
mentioning
confidence: 99%
“…The Pd catalyst in this case was taken over by Pt and Rh catalysts due to their higher stability upon sintering and their ability to maintain the active site unaltered during the treatment prior reaction and therefore. X. Auvray and A. Thuault [7] chose the Pt/Al 2 O 3 catalyst to study the effect of microwave pretreatment over precious metal dispersion. The microwave heating was compared to the conventional method of drying and calcination.…”
mentioning
confidence: 99%
“…This drying method can generate particles presenting different shapes and spatial structure, at wide-size range [2]. Some studies have been using vacuum microwave [8] and spray dryers [9,10] at the drying dispersion step; some authors have reported that spray drying use to obtain catalysts is an interesting method, since it improves particle morphology and is an efficient catalytic activity [9,10].…”
Section: Introductionmentioning
confidence: 99%